Lexy Lense / Faresya Zulaikha Khairul Anuar ... [et al.] - Khairul Anuar, Faresya Zulaikha; Ahmad Rizal, Nur Emiera Batrisyia; Ahmad Ibrahim, Nur Aina Fatini; Norhizam, Nur Amani Zahirah; Ahmad Tarmizi, Aernie Syamira; Azis, Siti Noraziana (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
Inside this project we examine a product designed expressly to meet the unique demands of dyslexic individuals in the context of writing and spelling. The tool includes predictive text algorithms, spell-checking functions, and word prediction capabilities to help with correct and efficient written communication. We investigated the product's usefulness in improving writing skill, lowering spelling errors, and increasing self-confidence among dyslexic users using user trials and expert evaluations. The research emphasizes the potential for technology-based interventions to empower people with dyslexia in academic and professional settings. The findings are helpful for educators, clinicians, and dyslexic people looking for effective literacy support methods.